Tantangan Agama di Era Globalisasi: Analisis Strategi Komunikasi, Karakteristik dan Materi Dakwah - Handaru, Bara Izzat Wiwah (Fakultas Dakwah dan Ilmu Komunikasi, Universitas PTIQ Jakarta, 2021)
The revolution in technology and communication media in this era of globalization has made the phenomenon of Islamic da'wah experience significant progress globally. This can be seen when the da'wah style has used advances in information technology so that the da'wah message is more widespread that is able to touch international aspects. But in reality, this change in pattern gave birth to new problems in the world of da'wah. This article tries to answer the main problems formulated in the major questions, namely; What are the challenges of religion in the era of globalization, using an analysis of communication strategies, characteristics and material for da'wah? According to Gill Branston and Roy Stafford (2010), there are several points explained about globalization. First, approaches to globalized media. Explain how to approach da'wah in the use of global media. Second, global–local flows. Explain how far the development of the flow of da'wah ideas that have reached the global world. Third, global futures? Explain how changes will occur in the world of da'wah in the future global era. In the end, the research provides insight into the topic of the problem in this paper. First, practically the da'wah movement in information technology and media in the era of globalization is based on Islam rahmatan lil 'alamin. Even though on the other hand, the impact of the globalization process related to religious life is the increasingly diminishing space for human religiosity itself. Second, the orientation in spreading da'wah globally is ukhuwah basyariyah which always fosters brotherhood among human beings. The attitude of humanism regardless of religious background, skin color and race. Third, have hope in the waiting period for the day to come (Al-Muntazhar). A principle that gives good news about a bright future and the implementation of all social justice for all mankind.